SSR marker development from peanut gynophore transcriptome sequencing. Issue 1 (23rd December 2015) - Zhong, Ruichun; Zhou, Meili; Zhao, Chuanzhi; Hou, Lei; Li, Changsheng; Wang, Xingjun; Tang, Ronghua; Xia, Han
Abstract: Peanut is one of the most important oil crops in the world. To accelerate the marker‐assisted selection programmes of peanut, a transcriptome library of peanut gynophores at three different growth stages was constructed and sequenced using Illumina HiSeq ™ 2000. Totally, 72 527 unigenes were assembled and mined for EST SSRs. A total of 5058 SSRs were obtained by using the SSR finding programme, which represented an average density of one SSR per 5.65 kb. Four thousand four hundred and forty‐two unigenes that contained one or more SSRs were identified. The most abundant SSRs in peanut are trinucleotides (55.1%) SSRs and followed by dinucleotides (33.2%). AG/CT (25.8%) repeats were the most abundant and followed by AAG/CTT (19.9%). Primers for 200 SSRs were designed for PCR amplification and for analysis of polymorphism in 22 peanut cultivars. Polymorphism could be detected by 17 SSRs among these cultivars. The newly developed SSR markers from peanut gynophore transcriptome sequencing will be an additional source of markers to the peanut community.